Supporting siblings during the critical illness hospitalization of a child: learning from experience - Dryden-Palmer, Karen; Shinewald, Alexis; O'Leary, Kimberly (Frontiers in Pediatrics, 2024)
Introduction: Childhood critical illness impacts the critically ill patient’s entire family. Disruption to usual family rhythms and routines, established relationships, physical relocations or shifts in caregivers and the uncertainty of the patient’s wellbeing, can result in significant impacts on siblings and other connected children in the family. Promoting and facilitating family interactions and engaging younger family members in the hospital experience has been shown to reduce patient and family anxiety, enhance family adaptation, and improve child and family outcomes. The critical care team can implement evidence-informed approaches to address and mitigate challenges for families and provide developmentally aligned support to impacted siblings. Aim: This conceptual paper describes the potential impacts of a critical illness hospitalization on siblings, approaches to supporting siblings and practical interventions drawn from a synthesis of the current literature and the author’s 90 years combined practice experience caring for critically ill children and their families. Data Sources: A traditional review and narrative analysis moderated by the authors and supported by lived experience. Conclusions: There is a range of impacts of a critical illness hospitalization on siblings and young family members of the patient. Providing consistent, transparent, and supportive child, sibling, and whole family-centered care can improve the experience and outcomes for the child and family.